A fault feature extraction method for rotating shaft with multiple weak faults based on underdetermined blind source signal. (6th November 2018) - Sun, Hongchun; Fang, Liang; Guo, Jingzheng
Abstract: In order to improve the fault feature extraction of a rotating shaft, an efficient method of underdetermined blind source signal with weak faults based on Hankel matrix-based singular value decomposition (SVD) and blind source separation (BSS) is proposed. First, a Hankel matrix is constructed for single-channel vibration signal, and then SVD is used to estimate the number of fault signals. Finally, the fault features can be extracted by BSS. Compared with wavelets, variational mode decomposition and ensemble empirical mode decomposition + BSS, the better performance of the proposed method is demonstrated by an analysis of the simulated signal with the misalignment fault and imbalance fault mixed. Furthermore, an experiment verifies the effectiveness of this method. The result demonstrates that the proposed method is efficient for feature extraction of a single-channel vibration signal of a rotating shaft with multiple weak faults.